'This land is my land, this land also is my land': real estate narratives in Pynchon's fiction. Issue 3 (16th March 2019) - Käkelä, Tiina
ABSTRACT: The question of land and land-ownership forms a constant thematic in Thomas Pynchon's work, and it can be traced back to his early fiction. In this paper, I'll focus on how Pynchon uses the land as a site of political and economic struggle between landowners and various propertyless people – squatters, indigenous peoples, refugees, settlers, hippies and anarchists. The analyses extend from The Crying of Lot 49 to Pynchon's latest novel, Bleeding Egde, where the struggle takes place in the immaterial spaces of the internet. To understand the role of land in Pynchon's work as both common and private, both sacred and commercialised, both material and virtual, I'll use the notion of common from Michael Hardt and Antonio Negri's Commonwealth (2009). My aim is to point out the recurring moments in Pynchon's fiction where common is the origin of wealth, and how private property stems from its exploitation. In Pynchon, however, the common always survives because of its versatility, recreating its form over and over again.